2007
DOI: 10.1149/1.2779968
|View full text |Cite
|
Sign up to set email alerts
|

A Diffusion and Reaction Related Model of the Epitaxial Lift-Off Process

Abstract: In the present work a so-called diffusion and reaction related model ͑DR model͒ is derived based on the notion that the overall etch rate in the epitaxial lift-off ͑ELO͒ process is determined both by the diffusion rate of hydrofluoric acid to the etch front and its subsequent reaction rate in the process. In contrast to the model that was previously described in the literature, the DR model yields etch rates which are in quantitative agreement with those obtained experimentally. In order to verify the DR model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…15 This mechanism is similar to that responsible for the etching of InP by undissociated HCl in acetic acid or concentrated aqueous solutions, 23 in which phosphine (PH 3 ) gas is formed. Niftrik et al 15 used a similar mechanism to explain the etching of AlAs in a HF solution; in that case the formation of AsH 3 was detected during the experiments. The arsine, formed in reaction 1, can give rise to elemental arsenic.…”
Section: Discussionmentioning
confidence: 86%
“…15 This mechanism is similar to that responsible for the etching of InP by undissociated HCl in acetic acid or concentrated aqueous solutions, 23 in which phosphine (PH 3 ) gas is formed. Niftrik et al 15 used a similar mechanism to explain the etching of AlAs in a HF solution; in that case the formation of AsH 3 was detected during the experiments. The arsine, formed in reaction 1, can give rise to elemental arsenic.…”
Section: Discussionmentioning
confidence: 86%
“…This could be the relatively slow or incomplete dissolution of reaction products under these particular conditions resulting in an accumulation of reaction products close to the etch front. 9 According to Eq. 1, the ELO process overall requires 3 moles of HF and 3-6 moles of H 2 O per mole of AlAs.…”
Section: ͓6͔mentioning
confidence: 99%
“…Unfortunately, we were unable to trace these data in the literature, so we now use instead data related to the solubility and diffusion of O 2 in water from Ref. 13 9 it is found that O 2 diffusion would limit the ELO etch rate to a maximum of only a few micrometers per hour if it was required in the dominant reaction with AlAs. Because the experimentally obtained etch rates are several orders of magnitude larger, it is clear that O 2 cannot be directly involved in this process.…”
Section: Influence Of Oxygen-previous Workmentioning
confidence: 99%
“…The attack of the substrate by the HF and the residues formed during the sacrificial layer etching result in the increase of RMS roughness from 0.3 to 1-4 nms range. Chemical reactions between AlAs and HF have been well studied 10,15,16 6 À n ] (3 À n) þ , on the other hand, are solid and hard to dissolve into the solution. Besides these primary byproducts, solid As 2 O 3 can also be generated on the substrate depending on the oxygen concentration of the etchant 17 .…”
Section: Resultsmentioning
confidence: 99%